The Reality of the Criminal Justice System in Independence of Law Enforcement Based on Pancasila Law System - Lindu Aji Saputro; Siti Rodhiyah Dwi Istinah; Siti Ummu Adillah (Universitas Islam Sultan Agung, 2022)
The purpose of this research is to find out how is the Independence of the Criminal Justice System by the law enforcement sub-system and how is the Reconstruction of the Independence of the Criminal Justice System. This research approach uses normative juridical. Based on the research, it is concluded that the independence of the National Police mainly lies in the implementation of